Thermo- economical consideration of Regenerative organic Rankine cycle coupling with the absorption chiller systems incorporated in the trigeneration system. (15th September 2017) - Anvari, Simin; Taghavifar, Hadi; Parvishi, Alireza
Highlights: A new trigeneration cycle was studied from a new viewpoint of exergoeconomic and thermodynamic. Organic Rankine and refrigeration cycles are used for recovery waste heat of cogeneration system. Application of trigeneration cycles is advantageous in economical and thermodynamic aspects. Abstract: In this paper, a combined cooling, heating and power cycle is proposed consisting of three sections of gas turbine and heat recovery steam generator cycle, Regenerative organic Rankine cycle, and absorption refrigeration cycle. This trigeneration cycle is subjected to a thorough thermodynamic and exergoeconomic analysis. The principal goal followed in the investigation is to address the thermodynamic and exergoeconomic of a trigeneration cycle from a new prospective such that the economic and thermodynamic viability of incorporating Regenerative organic Rankine cycle, and absorption refrigeration cycle to the gas turbine and heat recovery steam generator cycle is being investigated. Thus, the cost-effectiveness of the introduced method can be studied and further examined. The results indicate that adding Regenerative organic Rankine cycle to gas turbine and heat recovery steam generator cycle leads to 2.5% increase and the addition of absorption refrigeration cycle to the gas turbine and heat recovery steam generator/ Regenerative Organic Rankine cycle would cause 0.75% increase in the exergetic efficiency of the entire cycle. Furthermore, from total investment cost of the trigeneration cycle, only 5.5% and 0.45% results from Regenerative organic Rankine cycle and absorption refrigeration cycles, respectively.